Anticipation of thermal pain in diverticular disease. Issue 6 (11th March 2016) - Smith, J. K.; Marciani, L.; Humes, D. J.; Francis, S. T.; Gowland, P.; Spiller, R. C.
Abstract: Background: The relative importance of peripheral nerve injury or central pain processing in painful diverticular disease (DD) is unclear. Functional magnetic resonance imaging (fMRI) has demonstrated that dysfunctional central pain processing predominates in irritable bowel syndrome (IBS). This study aims to identify anticipatory changes in symptomatic DD (SDD) compared to asymptomatic DD (ADD) and IBS patients. Methods: Gastrointestinal symptoms and somatization were evaluated via the Patient Health Question‐12 Somatic Symptom and the SDD group divided into low (≤6 [LSDD]) and high (≥7 [HSDD]) somatization. Cued painful cutaneous thermal stimuli were delivered to the left hand and foot during fMRI. Fixed effect group analysis of the 'cued' anticipatory phase was performed. Key Results: Within the right posterior insula, greater deactivation was found in the ADD compared to other groups. In emotion processing centers, anterior and middle insula, greater activation was identified in all patient compared to the ADD group, and in LSDD compared to IBS and HSDD groups. In comparison, amygdala deactivation was greater in ADD than the IBS and HSDD groups, and in LSDD vs HSDD groups. Descending nociceptive control centers, such as the superior medial frontal and orbitofrontal cortex, also showed greater deactivation in the ADD and LSDD compared to the HSDD and IBS groups. Conclusions & Inferences: The HSDD group have altered anticipatory responses to thermal pain, similar to IBS group. The LSDD are similar to ADD group. This suggests underlying differences in pain pathophysiology, and the need for individualized treatment strategies to target the cause of their chronic pain. Abstract : Symptomatic diverticular disease patients can be separated into low (LSDD) and high (HSDD) somatization groups based on Patient Health Questionnaire‐12 (PHQ‐12 SS) During anticipation of pain greater deactivations occur (shown in blue) in somatosensory, emotional, and descending noxious inhibitory control pain regions in the asymptomatic (ADD) compared to the symptomatic diverticular disease (SDD) and irritable bowel syndrome (IBS) groups There are fewer anticipatory differences between the ADD and LSDD and the IBS and HSDD groups, suggesting the that LSDD and HSDD grouping identifies DD patients with predominantly peripheral vs central factors, respectively.